Production of String Bean (Vigna sinensis L.) as a Result of Bokashi Type Feeding and Pruning - Henny A. Raga (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Long beans (Vigna sinensis L.) have the potential to be developed because they have high economic value. However, this is not supported by a decrease in production availability for 5 years. One of the efforts made is to improve fertilization and pruning techniques. The aim of this research is to determine the interaction of bocation and pruning on long bean production. This research used a Randomized Block Design with a factorial pattern of 2 factors with 3 levels of treatment, namely: Factor I = Bokasi (B) consisting of B0 = No Bokasi (control), B1 = Bokasi solid cow dung 10 tons /haB2 = Bokasi dung solid pigs 10 tons/ha and B3 = liquid bokasi with a concentration of 1400 cc liters of water-1 plot-1 and Factor II = pruning (P) which consists of P0 = no pruning, P1 = pruning 21 HST and P2 = pruning 35 HST. The research results found that there was an interaction between giving bokasahi fertilizer (1,400 cc plot-1) and pruning time (21 HST) which had a very real influence and gave the best results on the research variables.